Prospective observational study to estimate set-up errors and optimise PTV margins in patients undergoing IMRT for head and neck cancers from a Government cancer centre of Eastern India. Issue 1 (9th July 2019) - Biswas, Priyanka; Lahiri, Debarshi; Roy, Sanjoy; Maji, Tapas; Bhadra, Kallol; Ray, Dilip Kumar; Das, Subhadip; De, Palas; Mohanta, Bijan Kumar
Abstract: Background: The head and neck cancers as a whole are the most common cancers among males in India. Technological advancements have led to an improvement in radiation therapy (RT) techniques with subsequent reduction in normal tissue complications. To correct patient set-up errors, an off-line correction method like no action level (NAL) protocol may be used as a preferred protocol particularly for a busy department. The objectives of the study were to measure the translational set-up errors using kV cone-beam computed tomography (CBCT) in patients undergoing intensity modulated radiotherapy (IMRT) in head and neck cancers and also to optimise clinical target volume (CTV) to planning target volume (PTV) margin using NAL protocol. Material and methods: On the first 5 days of RT, patient's position was verified by kV-CBCT and then weekly during the course of treatment. The comparison between the reference and kV-CBCT images was performed, and the shifts measured and recorded. The mean error from the initial five consecutive fractions was corrected on the sixth daily fraction. Displacements in all the directions were measured. The population systematic and random errors were determined and used to estimate PTV margins according to the van Herk formula. Results: A total of 322 images were analysed. Before correction, 15, 12 and 9% patients had systematic error ≥3 mm on X, Y and Z axes, but after correction this was reduced to 9, 0 and 0%. The total percentage of patients whose set-up margin was ≥5 mm before correction was 5, 6·25, 3·75%, but after correction it reduced to 1·88, 0, and 0·63%. The margins of total population were reduced to 63, 65 and 56% after correction on X, Y and Z axes, respectively. Conclusion: A simple off-line NAL protocol can correct the set-up errors without daily on-line imaging in patients undergoing IMRT and hence acting as a resource sparing alternative. Five millimetre margin to CTVs was adequate and safe to overcome the problem of set-up errors in head and neck IMRT.